Level and association of the general public knowledge and attitude on the role of technology in human trafficking: a quantitative study of Pakistan - Khan, Zeeshan; Mohammad Rahim Kamaluddin; Jamiah Manap; Surendran Rajaratnam; Masnizah Mohd; Chong, Ibrahim Maclean; Ratna Yunita Setiyani; Kalaivanan Syasyila (Penerbit Universiti Kebangsaan Malaysia, 2024)
Human trafficking activities have shifted from conventional methods to online platforms. This was a first-of-its-kind study that employed a quantitative cross-sectional study design to determine the level of general public knowledge and attitude, as well as the association between knowledge and attitude on the role of technology in human trafficking in Pakistan. For this study, a self-administered survey questionnaire was used to collect data from 443 participants from two provinces of Pakistan, namely Punjab and Khyber Pakhtunkhwa. The sample size was derived using the Raosoft online sample calculator and multi-stage sampling technique with inclusion and exclusion criteria. The data were analyzed using SPSS, employing descriptive statistics and Pearson correlation coefficient analysis. The results reveal that the majority of participants had a low level of knowledge, while their level of attitude was high on the use of technology in human trafficking. The result of the association between knowledge and attitude shows a strong correlation between knowledge and attitude. This study aims to significantly advance the understanding of this topic among academics, policymakers, and related security agencies through participation and collaboration with members of the local community. The stakeholders must leverage social media platforms to raise awareness about the ways in which human traffickers exploit technology. The findings of this study are also anticipated to enable the international community to achieve the UN Sustainable Development Goals (SDGs 2030), to focus on this new emerging issue to combat online human trafficking and safeguard the general public.